CONTROLLED RELEASE LAYERED MATRIX TABLETS OF ITOPRIDE HYDROCHLORIDE: IN VITRO AND IN VIVO EVALUATION - Sisinthy, Sreenivas Patro; Rao, Nalamolu Koteswara; Me, Bhanoji Rao (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: The tablets were prepared by wet granulation method using polyethylene oxide, which was used to prepare both the matrix core and barrier layers. In vitro dissolution studies were carried out on the developed formulations. Based on the dissolution data, the best formulation was chosen, and evaluated for its controlled release in healthy human volunteers. Results: When the dissolution data was analyzed, IMP3L2 has shown the highest R value (0.9866) with at least 80% of the drug released in 12 hrs among all the formulations. Hence, the formulation IMP3L2 was chosen as an ideal formulation and selected for in vivo studies in human volunteers. Eight healthy volunteers participated in the study, and a two-way crossover design was followed. The serum concentration of itopride hydrochloride was estimated by reverse-phase high-performance liquid chromatography. The pharmacokinetic parameters were calculated from the serum concentration of itopride hydrochloride versus time data. The delayed T max 2 , decreased K a , unaltered bioavailability, and prolonged t , indicated a slow and prolonged release of itopride hydrochloride from polyethylene oxide layered matrix tablets in comparison with the plain matrix tablet. Conclusion: Based on the results of in vitro and in vivo studies, it was concluded that polyethylene oxide based layered matrix tablets provided oral controlled release of itopride hydrochloride. Objective: In this study, layered matrix tablets of itopride hydrochloride were formulated using polyethylene oxide as release retardant to achieve a zero order drug release. The objective of the study was to develop a formulation which will release at least 80% of the drug in 12 hrs and show a correlation coefficient (R 2 ) value of at least 0.95. Keywords: Layered matrix tablets, Itopride hydrochloride, Polyethylene oxide, High-performance liquid chromatography, Serum.